DINAMIKA PELEMBAGAAN PARTISIPASI PEREMPUAN: STUDI KASUS DINAMIKA INISIASI PELEMBAGAAN PARTISIPASI PEREMPUAN DESA WONOLELO KABUPATEN BANTUL DALAM PERENCANAAN DAN PENGANGGARAN DAERAH - , TENTI NOVARI KURNIAWATI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Women's participation in local planning and budgeting process in the past 10 years in Indonesia continue to be encouraged and strengthened. The process indicates that the relation of state and citizen have started to improve and further towards a more democratic. This study aims to determine the degree of participation of women and initiation institutionalization women's participation Wonolelo Village, Bantul District in planning and budgeting process. This study uses a case study, data collection in this study using data collection methods of observation, interviews, and secondary data search. This study used a qualitative analysis. The results showed that degree of participation of women and initiation of institutionalization women's participation Wonolelo Village, Bantul District in planning and budgeting process existing at the level of the village and sub-district has achieved high quality information and genuine consultation. At the district level includes a discussion of budget planning (RAPBD) has reached the degree of effective participation of the advisory board (effective advisory body). Initiation of institutionalization women's participation in Wonolelo village on local planning and budgeting process is the process of building awareness through organizing, open access, encourage participation and control of budget policy. Initiation of institutionalization women's participation Wonolelo Village utilizing the popular spaces and invited spaces. On the one hand, the state provide formal space (invited spaces) so that citizen participation can be accommodated, but it is also accompanied by the community (civil society) to create its own space (popular spaces), which was formed in order to avoid interference from the state. Participation space is not the final space, but as an political arena that are contested. In the process, the initiation of institutionalization women's participation is influenced by three factors, namely the change of the values in the woman about the importance of women involved in the planning and budgeting process. The existence of women's revitalization organization, mechanisms and procedures for the participation of women through popular spaces and invited spaces and routine processes to encourage the initiation of the institutionalization women's participation through individual actors and organizations in the village Wonolelo and individual actors of the state institutions.